20230030 Financing and borrowing activities 2022 - European Investment Bank (European Investment Bank, 2024)
The European Investment Bank is the world’s biggest multilateral investor. This report lays out the EU bank’s priorities and details its investments in the projects that support those policy goals. The European Investment Bank devotes more than half its financing to climate action and environmental sustainability. The Bank aims to support the transition to renewable energy sources such as geothermal, hydroelectric, and wind power. Despite challenging investment conditions in the European Union, the European Investment Bank supports firms in their transitions to a greener economy and in addressing climate change. The report provides a breakdown of the European Investment Bank’s finance contracts signed within the European Union and beyond it, as well as information on financing and borrowing activities.